TERRITÓRIO, CIDADE-EMPRESA E RESPONSABILIDADE SOCIAL CORPORATIVA: O caso da CSN em Volta Redonda, RJ - Losicer, Carolina Dória Romeo (2013)
This research aims to analyze the practices of Corporate Social Responsibility, developed by the National Steel Company (Companhia Siderúrgica Nacional, CSN), in the city of Volta Redonda (Rio de Janeiro). Our focus is the impact of urban policy, generated by CSN s economic activities. To this end, a study is made on the territorial urban impacts by the installation of CSN in the city of Volta Redonda, comparing two models of corporate social responsibility, adopted by the same Company, in two periods : when it was a state enterprise (since the forties) and after its privatization, held in the nineties . We analyze the CSN s social and environmental impacts and the Company s posture before their effects. The aim is to contribute to the debate on the role of an industry in a given territory, from the conception of Corporate Social Responsibility. In this case study, it is possible to observe the intrinsic relationship between the territory of Volta Redonda and the CSN, featuring Volta Redonda as a company-town which remains highly susceptible and vulnerable to the industry s economic and social behavior.